Pelatihan Penggunaan Keamanan Siber Sistem Informasi Perusahaan dan Komunikasi Internal - Herdadi, Anintyo; Ayu, Ilmi Sila (ASOSIASI IDEBAHASA KEPRI, 2024)
Data security and information systems in a company are very important because they transport a company's data progress. Currently, there are many crimes in the field of technology, so a security system is needed so that data cannot be accessed and stolen by unauthorized people. The aim of this research is to provide outreach in training on the use of cyber security in a company. The right way to use to build security information in a company includes: 1. Making a study of policies regarding various information systems. Using an encryption system in data transfer 3. Choosing safe software for the organization 4. Increasing the security of passwords used .5 Implementing an Information Security Management System. Carrying out this service can help employees and company management of PT Unisystem Utama in maintaining data security from people who do not have the right to use data owned by the company.